Where to Look for the Morals in Markets? - Matthias Sutter; Jürgen Huber; Michael Kirchler; Matthias Stefan (Center for Economic Studies and ifo Institute (CESifo), 2016)
Markets are ubiquitous in our daily life and, despite many imperfections, they are a great source of human welfare. Nevertheless, there is a heated recent debate on whether markets erode social responsibility and moral behavior. In fact, competitive pressure on markets may create strong incentives for unethical practices (like using child labor) to increase competitiveness. While markets have been considered as detrimental for moral behavior, it has turned out a challenging task to identify where moral behavior is reflected in a market. Recent work has suggested that falling prices in markets with externalities are an indicator of declining morals. Here we examine the relation between trading volume, prices and moral behavior by presenting an experimental study where we let buyers and sellers interact on a double auction market. In one set of treatments, concluding a trade has no externality; in the other set, there is a negative externality by voiding donations for a potentially life-saving measles vaccine to UNICEF. We find that moral behavior reveals itself in lower trading volume in markets with an externality, but that market prices are hardly different between markets with or without an externality. We also vary the number of buyers and sellers and show that prices depend mainly on the relative number of buyers and sellers, but not on the existence of an externality. Hence, the market forces of supply and demand work equally well in determining prices whether or not trading has an externality.
Keywords: C92; D03; D62; 330; morals; markets; competition; experiment